2015
DOI: 10.1016/j.jep.2015.03.082
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering potential of Indonesian medicinal plants on glucose uptake enhancement and lipid suppression in 3T3-L1 adipocytes

Abstract: Screening of selected Indonesian medicinal plants has uncovered the potentials of E. longifolia Jack (root) and P. nigrum L. (fruits) with dual active functions, increasing insulin sensitivity through the enhancement of glucose uptake and reducing lipid accumulation in adipose cells. These findings suggest that the ability of both plants to suppress lipid production would provide additional benefits in the treatment of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 39 publications
1
30
0
2
Order By: Relevance
“…Therefore, the E. longifolia root extract has a potent anti-hypertriglyceridemia activity in rats. These reductions of TG may be associated with a previous in vitro report in which E. longifolia suppressed lipid accumulation in 3T3-L1 adipocytes [8].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, the E. longifolia root extract has a potent anti-hypertriglyceridemia activity in rats. These reductions of TG may be associated with a previous in vitro report in which E. longifolia suppressed lipid accumulation in 3T3-L1 adipocytes [8].…”
Section: Discussionsupporting
confidence: 83%
“…Despite wide range of traditional uses known, it is most solely for its aphrodisiac and anti-malarial properties [5][6][7]. Previous research shows that extracts from the roots of E. longifolia suppressed intracellular lipid accumulation in 3T3-L1 adipocytes, a treatment target for an anti-obesity agent [8]. Based on the previous study and traditional use, the present investigation was carried out to evaluate the antihyperlipidemic, anti-inflammatory and analgesic activities of E. longifolia root extract in animal models.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids as antioxidants that have the ability to capture free radicals, also have the potential to have an antidiabetic effect (Oguntibeju, 2014). Lahrita et al (2015) reported that the pasak bumi roots have the ability to increase insulin sensitivity in adipose, which plays an important role in the treatment of diabetes. Further research using the alloxan or streptozotosin induction model needs to be conducted to confirm the decreased activity of blood glucose level from methanol extract of the pasak bumi roots.…”
Section: Resultsmentioning
confidence: 99%
“…1 Indonesia has many plants that could serve as anti-diabetes and anti-obesity agents. 2 In Indonesia, people use Garcinia mangostana Linn. as a health supplement for preventing everything from ulcer, diarrhea, fever, hypertension, and obesity to diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%